Persebaran Sarana dan Prasarana Perpustakaan Sekolah Dasar Berbasis Sistem Informasi Geografis - Dhi Bramasta; Dedi Irawan (Khazanah Pendidikan, 2017)
AbstractThe aim of this research is to know the distribution of elementary school in Baturradensub-district of Banyumas Regency and to know the condition of library and facilities ofelementary school library in Baturraden Sub-district of Banyumas Regency. Theresearch was conducted in Baturraden Sub-district of Banyumas Regency. The subjectsof the study are primary school and the manager of elementary school library. Thisresearch is a qualitative descriptive research with spatial approach which is oneapproach in geography. Data collection techniques with observation, interview anddocumentation. Data analysis uses interactive analysis which includes reduction,display, verification and GIS. The results showed that the primary school distributionof Baturraden sub-district is clustered with distribution pattern following path oraccessibility path. The number of books and equipment in the library has not been inaccordance with the subjects and the number of students in the school, so that thecondition of the facilities and infrastructure of elementary school library in Baturradensub-district has not complied with the standard set by the government.Keywords: facilities and infrastructure, primary school library, geographic informationsystem